A hyphenated microLC-Q-TOF-MS platform for exosomal lipidomics investigations: Application to RCC urinary exosomes - Del Boccio, Piero; Raimondo, Francesca; Pieragostino, Damiana; Morosi, Lavinia; Cozzi, Gabriele; Sacchetta, Paolo; Magni, Fulvio; Pitto, Marina; Urbani, Andrea (Electrophoresis, 2012)
Urinary exosomes are released from every renal epithelial cell type facing the urinary space and therefore, they may carry molecular markers of renal dysfunction and structural injury. Here, we present a hyphenated microLC‐Q‐TOF‐MS platform for lipidomics studies applied to investigate the urinary exosome lipid repertoire. Lipids were separated by reversed‐phase chromatography using a linear gradient of formic acid 0.2% and tetrahydrofuran, in 40 min of analysis. Features (m/z with associated own retention time) were extracted by MarkerLynxTM (Waters) and processed, demonstrating good analytical performance in terms of repeatability and mass accuracy of the microLC Q‐TOF MS platform. In particular, a stable retention time (RSD less than 4%) and relative intensity (RSD from 2.9% to 11%) were observed. Moreover, the method takes advantages by the use of a lock spray interface (Waters) that allows readjusting the m/z data after acquisition, obtaining inaccuracy below 6 ppm in measuring the m/z value of the reference compound during chromatographic run. The method was employed in a preliminary application to perform comparative analysis from healthy control subjects and renal cell carcinoma (RCC) patients, in order to possibly highlight differences in lipid composition to be exploited as potential tumor biomarker. Differential lipid composition in RCC urinary exosomes was achieved and tentatively identified by accurate mass, providing a preliminary indication of a relationship between lipid composition of urinary exosomes and RCC disease. Among the total features significantly different in RCC exosomes, the ion at m/z 502.3 was taken as an example for molecular confirmation by MS/MS fragmentation analysis.